A Revision Restoring Projection after Nipple Reconstruction by Burying Four Triangular Dermal Flaps - Kim, Ji Hun (Arch Plast Surg, 2016)
BACKGROUND: Numerous techniques have been used to achieve long-term projection of the nipple following nipple-areola reconstruction. However, the reconstructed nipple loses projection over time. We describe a technique that uses local flaps to improve the lost projection of reconstructed nipples. METHODS: Between November 2013 and March 2015, nine patients (11 nipples) underwent revisional nipple reconstruction for lost projection. Only C–H nipple reconstructions were included in this study. The medical history of each patient was reviewed and photographs were taken in front and lateral views. All patients attended routine follow-up visits. Deepithelialized triangular flaps were made on all four sides of the nipple and buried in the opposite corners in order to augment the volume of the nipple. Anchoring sutures were used to attach each triangular flap on the side opposite their point of origin, and the resulting defects were closed directly. RESULTS: This procedure was used successfully in nine patients (11 nipples). Adequate projection was achieved in all patients and no complications occurred. The average nipple height was 3 mm before operation, 7 mm one day after operation, 5 mm at the six-month follow-up, and 5 mm at the 12-month follow-up. The average nipple-areolar angle was 164° before the operation, 111° one day after the operation, 130° at the six-month follow-up, and 133° at the 12-month follow-up. CONCLUSIONS: The method described provides a solution to the loss of projection in reconstructed nipples. We recommend this technique because it leads to better projection, greater volume, and a more natural shape.